Peringatan untuk Menguduskan Hari Sabat Keluaran 35:1-3 (Jurnal Pendidikan Agama dan Teologi, 2024)
The Sabbath is a pivotal theological concept in Christianity, established by God in the Decalogue (Exodus 20:4) and reiterated in Exodus 35:1-3. This study seeks to underscore the importance of sanctifying the Sabbath in the face of modern challenges that often prioritize work and worldly commitments. Employing a historical-critical method supported by theological literature and digital tools, this research explores the theological foundations of the Sabbath in Israelite tradition and its relevance to contemporary Christians. The Sabbath is more than a day of rest; it is a call to place God at the center of life, acknowledging that all blessings stem from Him. Observing the Sabbath enables Christians to achieve balance between worldly demands and spiritual well-being while strengthening their faith through worship and prayer